PEMBENTUKANKARAKTER PEDULI LINGKUNGAN SISWA SEKOLAH DASAR MELALUI SEKOLAH PEDULI DAN BERBUDAYA LINGKUNGAN - Widyaningrum, Ratna (Widya Wacana: Jurnal Ilmiah, 2016)
Education is important for the individual character formation. One of the characters that must beowned by an individual is the concern for the environment. Cultivate characters should be doneearly. Education in the Primary School is one of the foundations in developing the character ofstudents from an early age so that students have a strong character, intelligent, noble, and steadypersonality. Cultivate characters about the environmental care in the school can be done througha environmentally learning process, integrating environmental curriculum, extracurricularactivities, habituation related to the environment, school environment, and supported by theschool facilities that are environmentally friendly. School care and cultured environment can beused as one of the cornerstones in building the character of environmental care at the elementaryschool students.Keywords: Character Concerned about The Environment, Caring Schools and Cultured